Bound to the State – The Nobleman in Danish Politics. Issue 4 (November 2013) - Wendel-Hansen, Jens Lei; Møeller, Jes Fabricius
Bound to the State – The Nobleman in Danish Politics: Following an epoch of relative marginalisation during absolutism (1660–1848) the Danish landed elite and aristocracy experienced a remarkable political comeback during the early decades of constitutional government – especially in the period 1865–1894. Already during late absolutism the landed elite organised itself and made its voice heard in the assemblies of the estates (est. 1834). The aristocracy changed its strategy of legitimation and reconfigured itself from an estate defined by birth to a class defined by ownership of land. Blame for the defeat to the Prussian-Austrian coalition in the war of 1864 was almost exclusively put on the national liberal party and it paved the way for three decades of uninterrupted conservative rule. Between 1865 and 1897 the position of prime minister and member of cabinet was typically held by aristocrats and landed elite. The conservatives' power was based on stronger organisation than before, the support of the king and a majority in the first chamber of parliament, but it faced a serious challenge from the majority in the second chamber, the farmers' party Venstre.